Aplicación del pensamiento sistémico en el Proyecto Alianzas Salud Derecho en conjunto con el Departamento Nacional de Planeación (2020)
Due to the growing number of health guardianships presented annually in Colombia, the initiative was born to implement an artifact inspired by international models of medico-legal alliances. The purpose of this device is to provide legal advice to patients in such a way that pertinent solutions are found to the legal needs in health and in this way to decongest the judicial system. Thus, together with the National Planning Department (DNP), the Health-Law Alliance (ASD) model has been structured, which already has several stages of development. The current stage corresponds to the construction of the pilot plan for the population of Kangaroo Mothers of the Hospital Universitario Mayor Méderi (HUMM), for which the Uniandes team has offered support from the perspective of systems thinking. Systems thinking includes an iterative, collaborative, systemic approach and the implementation of Ulrich's Critical Systems Heuristics, tools that result in three deliverables. The first is the design of the strengthening and monitoring stages of the intervention, the second is the approach to the definition of legal empowerment relevant to this context together with a tool on how to measure it, and finally, the development of an implementation manual that has The purpose is to give scalability to the ASD program so that any institution providing health services (IPS) can include the initiative in their care center.